Strategic ESG-Driven HR Practices: Effects of ESG Integration on Employee Performance, Well-Being, and Human Capital Outcomes - I Dewa Ayu Tita Permata Tabita; I Gusti Agung Sasih Gayatri (Manunggal Halim Jaya, 2026)
The Balinese hospitality industry faces challenges in improving employee performance amidst global competition and increasing sustainability expectations. This study investigates how ESG (Environmental, Social, and Governance) practices integrated into HR strategies can improve employee performance and well-being. We developed a structural model that examines the causal relationships between Environmental Practices, Social Practices, Governance Practices, and Employee Performance & Well-Being. Using a quantitative cross-sectional approach with PLS-SEM (Partial Least Squares Structural Equation Modeling), we analyzed data from 366 permanent employees at 38 five-star hotels in Bali selected through stratified random sampling. The results showed that all seven hypotheses were statistically supported (p < 0.001) with R² = 0.944 for employee performance, indicating that social practices have the strongest direct effect on performance (β = 0.346), environmental practices most strongly encourage governance development (β = 0.472), and governance practices mediate approximately 30% of the total effects of ESG on performance. The model reveals dual influence mechanisms: intrinsic motivation pathways (70% dominant) and organizational justice pathways (30% complementary). Theoretical implications show that integrated ESG practices create competitive advantage through enhanced employee outcomes, with specific applications for developing country contexts. Managerial implications provide a four-phase strategic roadmap for implementing ESG-HR practices in hotels, with expected cumulative performance improvements of up to 80%. Hotels can achieve significant competitive advantages through superior employee performance, reduced turnover, enhanced reputation, and stronger sustainability positioning that create sustainable value for employees, organizations, and society.